Acute alcohol‐related dysfunction as a predictor of employment status in a longitudinal study of working‐age men in Izhevsk, Russia. (13th September 2013) - Cook, Sarah; DeStavola, Bianca L; Saburova, Lyudmila; Leon, David A
Abstract Aims To investigate longitudinally the effect of alcohol consumption and related acute alcohol‐related dysfunction on employment status. Design, setting and participants A total of 1143 men aged 25–55 years in regular paid employment and resident in the city of Izhevsk, Russia were interviewed between 2003–06 and then re‐interviewed (2008–09) and their employment status ascertained. Measurements Exposures of interest were baseline alcohol intake (yearly total volume of ethanol consumed and non‐beverage alcohols) and alcohol‐related dysfunction, measured by a latent variable defined in terms of frequency of alcohol‐related dysfunctional behaviours and by one or more episodes of zapoi (a period of continuous drunkenness lasting 2 or more days). The outcome of interest was whether or not men were still in regular paid employment at follow‐up. The inter‐relationship between these variables was investigated using structural equation modelling. Findings Total volume of ethanol consumed had no substantive effect on future employment status; however, taking into account education and other socio‐demographic factors, there was strong evidence that loss of regular paid employment at follow‐up was influenced by non‐beverage alcohol consumption [odds ratio = 2.30 for non‐beverage drinkers compared with beverage‐only drinkers, 95% confidence interval (CI) = 1.21, 4.40)], latent acute alcohol‐related dysfunction (odds ratio = 1.50 per standard deviation increase in dysfunction score, 95% CI = 1.20, 1.88) and zapoi (odds ratio = 3.08, 95% CI = 1.71, 5.55). Acute alcohol‐related dysfunction was an important mediator of the relationship between non‐beverage alcohol use and employment status. Conclusions Acute alcohol‐related dysfunction is an important factor in determining whether men remain in employment and an important mediator of the effects of alcohol intake.